Pemetaan Sistematis Trend Teknologi E-Business Untuk Sektor Logistic Dan Forwarding - Elfarosa, Ketut Vini; Dewi, Kadek Cahya; Kencanawati, AAA Mirah (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
This study aims to map research trends in the field of e-business technology for the logistics and forwarding sector. The study used a systematic mapping and systematic literature review approach. There were 3 research questions that are used as references in this study, namely: (1) What is the trend of research types on e-business technology for the logistics and forwarding sector?, (2) What is the trend of topics on e-business technology for the logistics and forwarding sector?, and (3) How is the mapping of e-business technology research for the logistics and forwarding sector based on research types and topics? The search focused on literature published in 2020-2024. The keywords are